Features of Biogenesis of Vesicles of External Membranes of Microorganisms, theirImmunogenic, Protective and Adjuvant Ability - N. D. Omelchenko; I. A. Ivanova; O. V. Duvanova; E. V. Shipko; A. V. Filippenko; A. A. Trufanova (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. The process of production of outer membrane vesicles by bacteria is the main mechanism in intercellular communication and an intermediary in relationships of a very different nature (symbiosis, commensalism and parasitism), therefore, the study of the role of vesicles in the pathogenesis and immunogenesis of bacteria is an important and timely task.Aims. The purpose of this research was the analysis of scientific publications Russian and foreign journals for the period from 2002 to 2021 from the bibliographic databases of eLibrary.Ru, PubMed®, MEDLINE, dedicated to vesicles of outer membranes formed in various types of pathogenic and non-pathogenic bacteria.Conclusion. The study of the structure, factors of formation, functional significance of the mechanisms of action of bacterial vesicles, as well as the role of these structures in the pathogenesis and immunogenesis of various diseases, including especially dangerous ones, makes it possible to create new preventive drugs based on them. The use of vesicles as means of delivery of biological drugs and various antigens opens up new opportunities for improving the therapy and prevention of infections.